Scale interactions and scaling laws in rotating flows at moderate Rossby numbers and large Reynolds numbers - Mininni, Pablo Daniel (2009)
The effect of rotation is considered to become important when the Rossby number is sufficiently small, as is the case in many geophysical and astrophysical flows. Here we present direct numerical simulations to study the effect of rotation in flows with moderate Rossby numbers (down to Ro ≈ 0.03) but at Reynolds numbers large enough to observe the beginning of a turbulent scaling at scales smaller than the energy injection scale. We use coherent forcing at intermediate scales, leaving enough room in the spectral space for an inverse cascade of energy to also develop. We analyze the spectral behavior of the simulations, the shell-to-shell energy transfer, scaling laws and intermittency, as well as the geometry and the anisotropy of the structures in the flow. At late times, the direct transfer of energy at small scales is mediated by interactions with the largest scale in the system, the energy containing eddies with k⊥ ≈ 1, where ⊥ refers to wavevectors perpendicular the axis of rotation. The transfer between modes with wavevector parallel to the rotation is strongly quenched. The inverse cascade of energy at scales larger than the energy injection scale is nonlocal, and energy is transferred directly from small scales to the largest available scale. We observe both a direct and inverse cascade of energy at high rotation rate, indicative that these cascades can take place simultaneously. Also, as time evolves and the energy piles up at the large scales, the intermittency of the direct cascade of energy is preserved while corrections due to intermittency are found to be the same (within error bars) as in homogeneous nonrotating turbulence. © 2009 American Institute of Physics.